(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
The article provides the results of 17 amino acids quantity determination in red beet-root grown with biostimulator containing the following bacteria – Azotobacter chroococcum, Bacillus subtilis, Bacillus megaterium and Trichoderma harzianum fungus. It was determined that applied biostimulator has contributed to the increased concentrations of all amino acids.